The XRE-DUF397 Protein Pair, Scr1 and Scr2, Acts as a Strong Positive Regulator of Antibiotic Production in Streptomyces - Santamaría, Ramón I.; Sevillano, Laura; Martín, Jesús; Genilloud, Olga; González, Ignacio; Díaz, Margarita (Frontiers in Microbiology, 2018)
The XRE (Xenobiotic Response Element) transcription factors belong to a regulator family frequently found in Streptomyces that are often followed by small proteins with a DUF397 domain. In fact, the pair XRE-DUF397 has been proposed to comprise toxin-antitoxin (TA) type II systems. In this work, we demonstrate that one of these putative TA-systems, encoded by the genes SCO4441 and SCO4442 of S. coelicolor, and denominated Scr1/Scr2 (which stands for S. coelicolor regulator), does not behave as a toxin-antitoxin system under the conditions used as was originally expected. Instead the pair Scr1/Scr2 acts as a strong positive regulator of endogenous antibiotic production in S. coelicolor. The analysis of the 19 Streptomyces strains tested determined that overexpression of the pair Scr1/Scr2 drastically induces the production of antibiotics not only in S. coelicolor, but also in S. lividans, S. peucetius, S. steffisburgensis and Streptomyces sp. CA-240608. Our work also shows that Scr1 needs Scr2 to exert positive regulation on antibiotic production.